2023
DOI: 10.1038/s41598-023-35091-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence mechanism of adoption of smart agriculture technology behavior

Abstract: Smart agricultural (SA) technology has become a technological support for modern agriculture. By exploring the decision-making process and psychological motivation of farmers in adopting SA technology, it is conducive to achieving the popularisation of SA technology and promoting the modernisation of agriculture. Based on microscopic research data, a Structural Equation Model (SEM) is used to analyse the influencing factors and extent of cotton farmers’ adoption of SA technologies, using Deconstructive Theory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 67 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Lazaridou et al [15] confirmed that farmers' willingness to use recycled water is linked to their perception of its environmental benefits. Additionally, previous research has shown that perceived usefulness is significantly associated with farmers' willingness to adopt smart farming technologies [64][65][66]. Based on these findings, this study will test the hypothesis that: H4: Perceived usefulness of water-smart farming has a significant influence on farmers' intentions to reduce water waste.…”
Section: Perceived Usefulness Of Water-smart Farming Technologiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Lazaridou et al [15] confirmed that farmers' willingness to use recycled water is linked to their perception of its environmental benefits. Additionally, previous research has shown that perceived usefulness is significantly associated with farmers' willingness to adopt smart farming technologies [64][65][66]. Based on these findings, this study will test the hypothesis that: H4: Perceived usefulness of water-smart farming has a significant influence on farmers' intentions to reduce water waste.…”
Section: Perceived Usefulness Of Water-smart Farming Technologiesmentioning
confidence: 90%
“…The social influence scale was adapted from Schrank et al [50] and Qalati et al [30]. Additionally, the PBC scale was drawn from Mouloudj et al [19] and Wang et al [53], and the perceived usefulness scale was obtained from Li et al [66]. As for the water waste reduction-related knowledge scale, it was modified from the scales used by Njoku et al [68] and Zhang et al [75].…”
Section: Measurement Of Constructsmentioning
confidence: 99%
“…A risk-neutral farmer is likely to adopt a technology that results in net increases in operating profits [42]. Many studies show that the perception of profitability with new technologies significantly drives the intention of adoption [31,34,37,38]. In addition to the profitability of alternative technologies, the riskiness of those profits can also impact the decisions of risk-averse farmers [33,35,38].…”
Section: Psychological and Behavioral Factorsmentioning
confidence: 99%
“…Many studies show that the perception of profitability with new technologies significantly drives the intention of adoption [31,34,37,38]. In addition to the profitability of alternative technologies, the riskiness of those profits can also impact the decisions of risk-averse farmers [33,35,38]. Since novel digital technologies often come with more economic uncertainty and technical difficulty than traditional ones, research has confirmed that the perceived ease of utilizing these technologies increases farmers' adoption of digital technologies [33,34].…”
Section: Psychological and Behavioral Factorsmentioning
confidence: 99%
“…However, while industrial digitization accelerates across sectors, the agricultural domain lags behind, with a meager 8.9% penetration rate of the digital economy. In contrast to the levels of digitization witnessed in secondary and tertiary sectors, the application of digital technologies in agriculture remains relatively limited in terms of quality and depth [ 2 ]. Certain areas with lower levels of development experience slower progress in digital rural development, while remote regions face challenges in establishing a conducive environment for digital infrastructure and Digital financial environment(DFE) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%